DAGESTAN PEOPLES' CONTRIBUTION TO VICTORY IN THE GREAT PATRIOTIC WAR OF 1941 - 1945 - Kajmarazov, G S (History, Archeology and Ethnography of the Caucasus, 2015)
Despite the large number of publications about the Great Patriotic War of 1941–1945 both on a nationwide scale and on the materials of the regions, this theme is currently important and inexhaustible taking into account its scientific, historical, social, political and practical significance. Particularly it is of vital importance today, when many scientists and a number of statesmen of the West as well, conduct anti-Russian propaganda and try to downgrade the role of the Soviet Union in the victory over Hitlerite, Nazi Germany. Basing on the experience accumulated by national historiography, using reliable sources and materials, the author of the article recreates a general picture of the contribution of the people of multinational Dagestan to the historic victory of the Soviet Union in the Great Patriotic War.The article shows patriotism of the Dagestan people, their determination to fight for freedom and independence of their Motherland, and gain victory over the treacherous aggressor. The article highlights the efforts to rebuild the whole life of the autonomous republic in the shortest possible time, the enthusiasm of workers on the home front, feats of arms of Dagestan soldiers at the front.The author of the article emphasizes that the success of the USSR peoples in the Great Patriotic War is one of the most striking and impressive pages of not only domestic but also world history. The historic victory over Nazi Germany became possible due to the combined efforts and heroism of all the peoples of our great multinational country.
Keywords: the Soviet Union; Russia; Dagestan; Red Army; Nazi Germany; treacherous aggression; rebuilding of life; patriotism; labor enthusiasm; heroism; courage; front; home front; industry; agriculture; education; culture; science; literature and art; mass media; press; health care